TINJAUAN ATAS PERKEMBANGAN PENDIDIKAN KEWARGANEGARAAN DALAM RUMPUN ILMU SOSIAL - Nastiti Mufidah (Institut Agama Islam Negeri Ponorogo, 2020)
The development of Citizenship Education is inseparable from the various other sciences that support it, including various sciences that come from the social sciences family. This article was written aimed at exposing the development of Citizenship Education in the social sciences, especially sociology and history, as well as the social sciences of humanities, namely political science and law. The development of Citizenship Education related to various social science families can be seen from the results of searches conducted by researchers based on reality and basic theories from experts. This research is in the form of a qualitative research with a literacy study which results in the conclusion that in its development Citizenship Education is indeed inseparable from the various sciences within the Social Sciences family as courses in Social Sciences are taught as inheritance from the Citizenship Transmission value. Social Sciences as the inheritance of the values of citizenship have the main objective in preparing students to become good citizens by using the values and culture of the nation as a foundation for developing their nation.